Uncovering theology : the depth, reach and utility of Australian theological education : [final report]. - Sherlock, Charles; Harding, Mark; Omerod, Neil; McIver, Robert; Moore, Gerard (Australian Learning and Teaching Council, 2009)
The main outcome of the Uncovering Theology project is a book of that title, of approximately 70,000 words, written by Dr Charles Sherlock, the Project Manager and published by ATF Press (Adelaide). The publisher has DEEWR recognition and has distribution networks across theology, nationally and globally, as well as within higher education. The Uncovering Theology project aims to scope tertiary theological education in Australia its depth, reach and utility. The intended broad outcome was a detailed, evidence-based portrait of the theology sector, in order to improve learning and teaching within it. The Project Team believes that this broad outcome has been achieved, and that the impact of Uncovering Theology will be highly significant for its main intended audience, Australian theological education, and the variety of churches, agencies, colleges and supporters involved. Australian theological education institutions welcome the warmer relationships developed over the past three decades with government and the universities, and believe that theology makes a distinctive contribution to higher education. Yet they continue to set their priorities by seeking to discern and follow the purposes of God, as revealed in Jesus Christ, not only for the sake of the churches, but for humankind in all its diversities, and the whole created cosmos. [Executive summary, ed]